2004
DOI: 10.1038/sj.sc.3101577
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia-induced transient visual disturbances in acute spinal cord injury

Abstract: Study design: Case report and literature review. Objective: To report an unusual case of prolonged hyponatremia in acute cervical spinal cord injury complicated by visual disturbances and to review the literature regarding the issue. Settings: Spinal Cord Injury Unit in Go¨teborg, Sweden. Methods: Retrospective analysis of clinical charts of an individual with traumatic spinal cord injury. Results: A previously healthy 28-year-old man sustained a C7 injury in a motor vehicle accident. His injury was managed su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…25,74 Hyponatremia is also reported in acute SCI. 75 Thus, hyponatremia, probably secondary to supraphysiological ADH activity in SCI, 51 is common among acute and chronic SCI patients. 25,75,76 The combination of increased ADH secretion, low sodium intake, high sodium excretion and the resulting hyponatremia are likely to predispose towards small plasma volumes in SCI patients, and this, in turn, would exacerbate episodes of orthostatic hypotension in these individuals.…”
Section: Altered Salt and Water Balancementioning
confidence: 99%
“…25,74 Hyponatremia is also reported in acute SCI. 75 Thus, hyponatremia, probably secondary to supraphysiological ADH activity in SCI, 51 is common among acute and chronic SCI patients. 25,75,76 The combination of increased ADH secretion, low sodium intake, high sodium excretion and the resulting hyponatremia are likely to predispose towards small plasma volumes in SCI patients, and this, in turn, would exacerbate episodes of orthostatic hypotension in these individuals.…”
Section: Altered Salt and Water Balancementioning
confidence: 99%
“…32 In patients with chronic SCI, there is evidence of impaired water and sodium retention, which is confounded by limited salt and water intake. 33 There is only limited information available on circulating volume following SCI; however, it has also been shown that total blood volume and hemoglobin mass are decreased in individuals with SCI with a lesion above T4. 34 The combination of increased antidiuretic hormone secretion, low sodium intake, high sodium excretion and resultant hyponatremia are likely to predispose toward lower plasma volumes in patients with SCI.…”
Section: (Figures Reprinted With Permission)mentioning
confidence: 99%
“…A decrease in tear production can result in dry eye syndrome that can produce things like ocular surface damage (Dartt, 2004;Stern et al, 2004). Decreases in visual acuity have been shown post-SCI and is thought to be due to the increased risk of hyponatremia within the SCI population compared to able-bodied individuals (Barletta et al, 1994;Giordano et al, 2000;Karlsson and Krassioukov, 2004).…”
Section: Visual Systemmentioning
confidence: 99%